2013
DOI: 10.1016/j.jacc.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-B-Type Natriuretic Peptide and Its Relationship With Cardiac Function in Adults With Congenital Heart Disease

Abstract: NT-proBNP levels in adults with CHD clearly differ by diagnosis and are related to echocardiographic parameters and exercise capacity. Disease-specific correlations contribute to the understanding of the main hemodynamic problems per diagnosis. Follow-up data are needed to elucidate the additional prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…As we know patients with aortic stenosis or coarctation often have diastolic dysfunction, we had expected higher MMP-2 levels in these patients (Eindhoven et al, 2013). Neither did we find significant relations with aortic dimensions as measured by echocardiography, although a trend was observed for MMP-2 (adjusted p value 0.087).…”
Section: Aortic Stenosis and Dilatationmentioning
confidence: 62%
See 1 more Smart Citation
“…As we know patients with aortic stenosis or coarctation often have diastolic dysfunction, we had expected higher MMP-2 levels in these patients (Eindhoven et al, 2013). Neither did we find significant relations with aortic dimensions as measured by echocardiography, although a trend was observed for MMP-2 (adjusted p value 0.087).…”
Section: Aortic Stenosis and Dilatationmentioning
confidence: 62%
“…In line with these results, Chen et al (2013) recently reported that a serum biomarker of collagen type I synthesis (carboxy-terminal propeptide of procollagen type I, PICP) was related to higher RV late gadolinium enhancement scores (indicating myocardial fibrosis) and lower peak oxygen uptake in patients with repaired tetralogy of Fallot. Diastolic function is often impaired in adults with CHD (Eindhoven et al, 2013). Diastolic dysfunction is especially common in patients with congenital aortic stenosis (Dusenbery et al, 2014;Friedman et al, 2013).…”
Section: Cardiac Functionmentioning
confidence: 99%
“…84,85 A large study of ACHD patients revealed that N-terminal pro-BNP levels differed by diagnosis, being the highest in patients with Fontan circulation and a systemic RV. 86 In a systematic review, BNP levels were increased in complex CHD, with a clear association between BNP levels and New York Heart Association functional class. 87 Overall, BNP levels that suggested increased risk were low and quite different from those seen in acquired HF.…”
Section: Prognosismentioning
confidence: 99%
“…Patient demographics, medical history, medication use, symptoms and signs of heart failure (NYHA classification), results of physical examination, associated lesions, surgical characteristics, re-interventions, electrocardiography, echocardiography, laboratory results and events were collected using an electronic CRF-based online system (© 2004-2012 OpenClinica, LLC and collaborators). Details have been reported previously [11]. The institutional review board of the Erasmus MC approved the study protocol and all participants provided written informed consent.…”
Section: Study Design and Populationmentioning
confidence: 99%